2022
DOI: 10.3390/antibiotics11070941
|View full text |Cite
|
Sign up to set email alerts
|

Co-Administration of Remdesivir and Azithromycin May Protect against Intensive Care Unit Admission in COVID-19 Pneumonia Requiring Hospitalization: A Real-Life Observational Study

Abstract: The benefits of remdesivir treatment, with or without co-administration of antibiotics such as azithromycin, are uncertain in COVID-19 pneumonia. The aim of this retrospective single-center study was to assess the effects of remdesivir, with or without azithromycin, on hospital mortality, intensive care unit (ICU) admission, and need of non-invasive ventilation. The clinical records of the COVID-19 patients hospitalized in an Italian ward in March 2021 were analyzed, and data on comorbidities and clinical, rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Similarly, combining antivirals might lead to synergy and complete inhibition of SARS-CoV-2, the causative agent of the COVID-19 pandemic, especially when attacking the virus at multiple steps of its life cycle by broad-spectrum antivirals acting with different mechanisms of action such as RDV, AZI and IVM. In line with our hypothesis and proposed mechanism of action, a recent clinical study at the hospital of Parma, Italy, one of the first provinces hit by COVID-19 outside China in early 2020, showed that intensive care unit admission was significantly delayed by the combination of AZI and RDV, but not by RDV alone, in a stepwise multivariate logistic regression model [17].…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, combining antivirals might lead to synergy and complete inhibition of SARS-CoV-2, the causative agent of the COVID-19 pandemic, especially when attacking the virus at multiple steps of its life cycle by broad-spectrum antivirals acting with different mechanisms of action such as RDV, AZI and IVM. In line with our hypothesis and proposed mechanism of action, a recent clinical study at the hospital of Parma, Italy, one of the first provinces hit by COVID-19 outside China in early 2020, showed that intensive care unit admission was significantly delayed by the combination of AZI and RDV, but not by RDV alone, in a stepwise multivariate logistic regression model [17].…”
Section: Introductionsupporting
confidence: 85%
“…Our results would suggest the possibility of once-a-day (QD) administration may be effective for any of these combinations. A clinical study submitted after our study had been submitted and published while our manuscript was under review found that the coadministration of RDV and AZI was associated with reduced risk of ICU admission, independently of covariates [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Intravenous dexamethasone treatment has rapidly gained the role of cornerstone treatment of COVID-19 related interstitial pneumonia, for its capacity of reducing mortality, oxygen supplementation and ventilatory support need ( 32 ). Intravenous remdesivir was also commonly used during the third wave, but not in the first one ( 33 ). Interestingly, the higher frequencies of NIV support and ICU treatment detected in the third wave ( Table 1 ) could reflect improved management protocols and better understanding of indications and timing of ventilatory escalation in patients with severe respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Du et al reported azithromycin demonstrated in vitro anti-viral effect against SARS-COV-2 and blocks the entry of SARS-CoV-2 in HEK293T-ACE2 and Caco2 cells [26]. Another observational study also reported the clinical benefits of antibiotics: the combination of remdesivir-azithromycin treatment significantly decreased the ICU admission rate [27]. However, the exact mechanism of antibiotics in SARS-COV-2 viral clearance remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%